Kajian Ekologis Rafflesia Patma Blume di Cagar Alam Leuweung Sancang Jawa Barat - Dadang R Priatna; Ervizal A. M Zuhud; Hadi S Alikodra (Department of Forest Resources Conservation and Ecotourism - IPB University, 1989)
Rafflesia parma Blume is one of the 12 Rafflesia spp. found in Indonesia which has an attractive and relatively big flower and a unique life. As a holoparasite, this astonishing plant is particularly dependent on the distribution of, and its interaction with the liana host, Tetrasfigma sp.The distribution of R. patma is confined to the Leuweung Sancang Nature Reserve, the Pananjung Pangandaran Nature Reserve and the Nusa Kambangan Nature Reserve. The people in Java andKalimantan have been utilizing Rafflesia for traditional bio-medicine (such as for the raw material of jamu